Identification of Quantitative Trait Loci for Fiber Quality Properties on Homoeologous Chromosomes 13 and 18 of Gossypium klotzschianum. Issue 2 (1st March 2014) - Xu, Peng; Cao, Zhibin; Zhang, Xianggui; Gao, Jin; Zhang, Xia; Shen, Xinlian
ABSTRACT: Exotic Gossypium germplasms are rich sources of useful agronomic traits for cultivated cotton improvement programs. The efficient use of genetic variation available in the wild relatives depends on the ability to identify and introgress their desirable DNA segments from wild species into cultivated cotton. To introgress favorable genes from G. klotzschianum into G. hirsutum, a BC1 F2 population derived from (Simian 2 × G. klotzschianum ) × Simian 2 was constructed. Single marker analysis showed that the simple sequence repeat (SSR) markers BNL2652, NAU1201, and NAU1141 on chromosome 13 were significantly correlated with fiber length and micronaire value in a small BC1 F2 –derived population. To confirm the genetic effects of G. klotzschianum loci on fiber quality, the BC2 F3 and BC2 F4 populations (716 individuals/lines) were then developed by crossing BC1 F2 individuals containing target segments of chromosome 13 from G. klotzschianum to the recurrent parent Simian 2. In total, 171 SSR markers from chromosome 13 and its homoeologous chromosome 18 were used to analyze the BC2 F3 population. A total of 8 quantitative loci (QTL), 3 for fiber length, 2 for miconaire, and 3 for fiber strength, were detected on these two chromosomes. The fiber length QTL identified in the BC1 F2 population, qFL‐13–1, was confirmed in the BC2 F3 and BC2 F4 populations, which accounted for 7.3 and 7.0% of the phenotypic variance, respectively. The G. klotzschianum allele increased fiber length. The QTL for fiber micronaire detected in the BC1 F2 population, qFMIC‐13–1, was also confirmed in the BC2 F3 and BC2 F4 populations, which accounted for 11.2 and 7.2% of the phenotypic variance, respectively. The G. klotzschianum allele decreased the micronaire value. Two other QTL on chromosome 18 for fiber length ( qFL‐18–2 ) and micronaire ( qFMIC‐18–1 ) were also detected in both generations. Furthermore, a pair of putative homoeologous QTL for fiber length, qFL‐13–1 and qFL‐18–2, was identified. This study showed that some G. klotzschianum loci associated with fiber quality can be successfully transferred into upland cotton and display genetic stability.